Ramucirumab Plus Pembrolizumab in Patients with Previously Treated Advanced or Metastatic Biliary Tract Cancer: Nonrandomized, Open‐Label, Phase I Trial (JVDF). (31st May 2018) - Arkenau, Hendrik‐Tobias; Martin‐Liberal, Juan; Calvo, Emiliano; Penel, Nicolas; Krebs, Matthew G.; Herbst, Roy S.; Walgren, Richard A.; Widau, Ryan C.; Mi, Gu; Jin, Jin; Ferry, David; Chau, Ian
Abstract: Lessons Learned: Ramucirumab plus pembrolizumab revealed no unexpected safety findings in patients with advanced or metastatic biliary tract cancer, which is consistent with reports of other tumor cohorts within this phase Ia/b trial. Ramucirumab plus pembrolizumab did not demonstrate an improvement in overall survival when compared with historical controls in biomarker unselected, heavily pretreated patients with advanced or metastatic biliary tract cancer. Patients with programmed death‐ligand 1 (PD‐L1)‐positive tumors had improved overall survival compared with patients with PD‐L1‐negative disease. Background: Few treatment options exist for patients with advanced biliary tract cancer (BTC) following progression on gemcitabine‐cisplatin. Preclinical evidence suggests that simultaneous blockade of vascular endothelial growth factor receptor 2 (VEGFR‐2) and programmed death 1 (PD‐1) or programmed death‐ligand 1 (PD‐L1) enhances antitumor effects. We assessed the safety and efficacy of ramucirumab, an IgG1 VEGFR‐2 antagonist, with pembrolizumab, an IgG4 PD‐1 antagonist, in biomarker‐unselected patients with previously treated advanced or metastatic BTC. Methods: Patients had previously treated advanced or metastatic adenocarcinoma of the gallbladder, intrahepatic and extrahepatic bile ducts, or ampulla of Vater. Ramucirumab 8 mg/kg was administered intravenously on days 1 and 8 with intravenous pembrolizumab 200 mg on day 1 every 3 weeks. The primary endpoint was safety and tolerability of the combination. Secondary endpoints included objective response rate (ORR), progression‐free survival (PFS), and overall survival (OS). Results: Twenty‐six patients were treated at 12 centers in five countries. Hypertension was the most common grade 3 treatment‐related adverse event (TRAE), occurring in five patients. One patient experienced a grade 4 TRAE (neutropenia), and no treatment‐related deaths occurred. Objective response rate was 4%. Median progression‐free survival and overall survival were 1.6 months and 6.4 months, respectively. Conclusion: Ramucirumab‐ pembrolizumab showed limited clinical activity with infrequent grade 3–4 TRAEs in patients with biomarker‐unselected progressive BTC.